The Effect of Intellectual Capital on Fair Value of Shares: Evidence from Indonesia’s Basic Materials Sector - Ryna Sri Sulistyorini; Noto Pamungkas; Retno Yulianti (AIBPM Publisher, 2025)
Intellectual capital, which includes intangible assets such as knowledge, innovation, and organizational capability, plays a critical role in influencing firm performance and valuation, particularly in knowledge-intensive industries. This study aims to examine the effect of intellectual capital on the determination of fair value of shares in companies operating in the Basic Materials sector. The study uses a quantitative approach with multiple linear regression analysis applied to a sample of 132 observations from 46 companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023. The fair value of shares is measured using the Price Earnings to Growth (PEG) ratio, while intellectual capital is assessed through its three key components: human capital, structural capital, and relational capital. The findings provide empirical evidence that intellectual capital has a significant and positive impact on the fair value of shares. Among the control variables, leverage shows a negative effect, while firm size does not significantly influence fair value. The study concludes that intellectual capital should be strategically managed and disclosed, as it contributes to market valuation. These results offer valuable implications for investors, regulators, and company management in developing more comprehensive valuation models in emerging markets.